INTIMA-MEDIA THICKNESS OF CAROTID ARTERIES IN PATIENTS WITH CORONARY ARTERY DISEASE COMBINED WITH ARTERIAL HYPERTENSION - Аbduyeva, F.M.; Sheptun, A.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Prevalence in the modern cardiological practice of CAD combined with AH makes this problem topical. To investigate IMT of carotid arteries (CA) in patients with CAD combined with AH 60 patients (54,2±8,7) were examined. They were sorted in the following: examination group – 31 patient with CAD+AH (57,4±10,0); 2 comparative subgroups – 5 patients with CAD (54,7±6,6) and 24 patients with (AH 54,7±6,6) and control group - 8 young volunteers (27,3±6,0).The results demonstrate association of CAD with increased IMT CA independently of presence or absence of AH. Thus the main contributor to increase of IMT in patients with CAD+AH is believed to be atherosclerosis but not AH.